Dynamic Balance Evaluation: Reliability and Validity of a Computerized Wobble Board. Issue 6 (June 2020) - Fusco, Andrea; Giancotti, Giuseppe F.; Fuchs, Philip X.; Wagner, Herbert; Varalda, Carlo; Capranica, Laura; Cortis, Cristina
Abstract : Abstract: Fusco, A, Giancotti, GF, Fuchs, PX, Wagner, H, Varalda, C, Capranica, L, and Cortis, C. Dynamic balance evaluation: reliability and validity of a computerized wobble board. J Strength Cond Res 34(6): 1709–1715, 2020—Computerized wobble boards (WBs) are inexpensive, transportable, and user-friendly devices to objectively quantify the dynamic balance performances out of laboratory settings, although it has not been established if they are reliable and valid tools. Therefore, the purpose of this study was to determine the reliability and validity of a computerized WB. Thirty-nine (18 females and 21 males) young adults (age: 23.3 ± 2.1 years; body mass: 65.9 ± 1.8 kg; height: 168.2 ± 8.8 cm; leg length: 78.8 ± 5.7 cm; and body mass index: 23.2 ± 2.1 kg·m −2 ) participated in the study. Subjects were assessed during 3 separate sessions on different days with a 48-hour rest in between. A total number of 2 WB single limb tests and 1 Y Balance Test (YBT) were performed. The WB performance was registered using the proprietary software and represented by the time spent in the target zone, which represented the 0° tilt angle measured by the triaxial accelerometer in the WB. YBT normalized reach distances were recorded for the anterior, posteromedial, and posterolateral directions. Intraclass correlation coefficient, 95% confidence interval, SEM, minimal detectable change, and Bland-Altman plots were used to evaluate intrasession and intersession reliability, whereas Pearson product moment correlation was used to determine concurrent validity. Reliability ranged from fair to excellent, showing acceptable levels of error and low minimal detectable change. However, all correlation coefficients between WB and YBT outcomes were poor. Despite the 2 methods addressing different aspects of balance performance, WB seems to validly serve its purpose and showed good reliability. Therefore, computerized WBs have the potential to become essential devices for dynamic balance assessment.